2014
DOI: 10.1002/jssc.201301348
|View full text |Cite
|
Sign up to set email alerts
|

Retention behavior of a homologous series and positional isomers of aliphatic amino acids in hydrophilic interaction chromatography

Abstract: The retention behavior of several series of free α- and ω-amino acids and positional isomers of amino pentanoic acid in the hydrophilic interaction chromatography mode (HILIC) was studied. The study was carried out on three stationary phases followed by post-column derivatization with fluorescence detection in order to describe the retention mechanism of the tested amino acids. The effect of chromatographic conditions including acetonitrile content in the mobile phase, mobile phase pH (ranging from 3.5 to 6.5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The order of retention of amino alcohols corresponded well to their log P values (Table ). Compounds with higher log P value are less hydrophilic and as a consequence less retained in HILIC mode .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of retention of amino alcohols corresponded well to their log P values (Table ). Compounds with higher log P value are less hydrophilic and as a consequence less retained in HILIC mode .…”
Section: Resultsmentioning
confidence: 99%
“…The separation and quantitation of amino acids and amines including ethanolamine was carried out in a single run as their OPA/3‐mercaptopropionic acid or OPA/ N ‐acetyl ‐l‐ cysteine derivatives . One possible approach for separation of aliphatic amines, amino acids, and amino alcohols without precolumn derivatization step is HILIC [].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al investigated the retention mechanism of tetracyclines on an amino bonded silica phase and found that partitioning was a significant mechanism, especially in the range of 20-50% water, but adsorption and electrostatic interactions were also involved. 24 The elution order of the homologous amino acids correlated with the carbon number of the aliphatic chain, but no significant difference was observed when the retention data of both αand ω-amino acids was fitted to the partitioning and adsorption models. 23 More recently, Douša et al investigated the retention of a homologous series of aliphatic αand ω-amino acids on three polar stationary phases including an amide (TSKgel Amide-80), a diol (Kromasil 60-5DIOL) and an amino (Nucleosil 100-5 N(CH 3 ) 2 ) phase.…”
Section: Recent Investigations In the Retention Mechanismmentioning
confidence: 94%
“…24 Chirita et al conducted an investigation on the retention mechanism by testing a large set of 76 compounds (anionic, cationic, neutral and zwitterionic) on two zwitterionic stationary phases (ZIC-HILIC and Nucleodur HILIC). Douša et al found a linear correlation (r > 0.99) between log k and log D for the α-amino acids at pH 3.5-6.5 and for the ω-amino acids at pH 3.5 on three polar phases (TSKgel Amide-80, Kromasil 60-5DIOL, Nucleosil 100-5 N(CH 3 ) 2 ).…”
Section: Recent Investigations In the Retention Mechanismmentioning
confidence: 99%
“…A HILIC–MS method has the advantage of enhanced detection sensitivity and ESI efficiency due to its high organic content eluting solvent, which also provides low column backpressure because of low viscosity in mobile phase. HILIC can be a complementary alternative to separate highly polar compounds that are not retained or elute too early in RPLC .…”
Section: Introductionmentioning
confidence: 99%